The development of a real time supervision less Arduino’s trainer board for engineering technology undergraduate program - Zainal Abidin, Amar Faiz; Mohd Harun, Arfah Hafieza; Mohamad, Syahrul Hisham; Mohd Said, Rahaini; Widiyanto, Sigit (Research and Scientific Innovation Society, 2025)
Arduino has been widely used as the default microcontroller for teaching and learning due to its cost-effective and user-friendly features. This is evident from the many commercial Arduino trainers available on the market. Unfortunately, all these trainers require supervision, limiting the teaching and learning sessions to a small number of students. This project aims to create a proof-of-concept for an Arduino Trainer that can provide automatic feedback on whether students correctly connect the components. This trainer consists of an Android app and a trainer board. The Android app will display the required component connections in the form of questions and provide feedback by automatically checking the connections made by the students. The trainer board includes eight of the most commonly used electronic components. The proof-of-concept is then verified by comparing the expected results with the actual results obtained from the trainer. Additionally, a survey among the students is conducted for the validation process. The survey results indicate the potential use of the trainer to aid teachers in teaching and learning sessions.